Methodologies to Reduce Cooling Load using Heat Balance Analysis: A Case Study in an Office Building in a Tropical Country. (August 2015) - Nazi, Wan Iman Wan; Wang, Yao Dong; Roskilly, Tony
Abstract: The world is experiencing energy crisis since the 1970s due to the limitation in fossil fuel resources and increasing energy demand as a result of industrialisation and development which have taken place all over the world [1]. It is reported by International Energy Agency (IEA) that 32% of the total worldwide energy consumption was contributed by building sector [2]. Researchers found that Heating Ventilation and Air Conditioning (HVAC) system consumed the highest amount of energy in commercial building [3–7] meanwhile in tropical countries more than 50% of the building's energy were used for air conditioning [8]. This research found that standard building can be transformed into Low Energy Office building by applying heat gain reduction methodologies draws from heat balance analysis. An office building in Malaysia was audited and modelled in Design Builder software for heat balance analysis. It is found that 75% of the building's heat gain was radiated from lighting system and solar heat gain through window. It is estimated that 45.85% of building's energy can be saved by changing the zones temperature set point, modification in lighting system and building's glazing for daylight optimization and minimizing solar heat gain. Besides energy saving, the building's indoor environmental quality based on MS1525:2007 and occupants' comfort was ensured too. A basic cost analysis estimated in the software shows that the highest increment in initial cost for the methodologies suggested was only 1.32%, hence this study shows that a sustainable building does not necessarily induced high cost for the technologies implementation if the right technologies were chosen to suit the building's condition.